Perception Of Pre-clinical Students Towards Doctors Lifestyle - Shalinawati Ramli; Khairani Omar; Zarini Ismail; Nur Syahrina Rahim; Nurul Hayati Chamhuri; Nurul Azmawati Mohamed @ Abd Aziz (World Academy of Science, Engineering and Technology, 2024)
Medical doctors’ work to prevent, diagnose, treat diseases, disorders, and injuries as well as prescribing medication. Many people are attracted to this profession because it gives them the opportunity to help others. Doctors’ improve quality of life by providing advice, healing physical ailments and performing complex surgeries. Medicine is a profession in which dedication to the wellbeing of others is of paramount importance. Balancing the requirements of work and personal life can be a struggle as the demand of work as a doctors’ is great. Perception and expectation of medical students regarding the lifestyle of doctors’ is important to ensure that they had made the right career choice. Thus, the aim of this study is to assess the perception of pre-clinical students regarding doctors’ lifestyle. This study is a cross-sectional study involving all third-year pre-clinical medical students at University Sains Islam Malaysia. A total of 81 students participated in this study. Participants were given a set of questionnaire consisting of demographic data, open-ended questions on their perception on doctors’ lifestyle of working environment, salary expectation and family life. Thematic analysis were used to analyse the data. The participants comprised 69% female and their age range was between 20-21 years old. Majority of them were from middle income families. Majority of the students perceived that the doctors’ lifestyle would be busy (72%). Approximately 30% of them expected that the time schedule will be unpredictable, 21% mentioned that sacrifice is required and 16% perceived it as a tiring job. Other themes emerged were ‘requiring high commitment’ (6%), challenging (7%) and risky (4%). With regards to salary expectation, 48% expected reasonable salary, 33% high salary and 12% described it as 'not worth compared to the workload'. Majority of them perceived that their family life will be restricted (62%) and time management is important (33%). Only 15% mentioned that family members have to sacrifice and spousal understanding is important (7%). About 10% of them perceived that their family will not be affected by their profession. Majority of the medical students perceived a busy doctors’ lifestyle, reasonable salary and restricted family life. However, there was a significant proportion of them who required counselling for better preparation of their future lifestyle.